Optimization and Modification of the Hydrogen Peroxide to Propylene Oxide (HPPO) Process - Fikri Wisnu Pratama; Zaidan Fadhlan; Thariq Abrar Purnamadjati; Wisnu Satrio Adjie (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
The production of Propylene Oxide (PO) through the Hydrogen Peroxide to Propylene Oxide (HPPO) process represents a cleaner and more efficient route compared to conventional methods. This project focuses on the design and feasibility of a chemical plant with an annual capacity of 10,000 tons of PO using propylene and hydrogen peroxide as feedstocks. The HPPO process, catalyzed by a titanium silicate (TS-1) catalyst, offers significant environmental and economic advantages, such as reduced by-products and lower energy consumption. The core reaction occurs in a convergent reactor under mild operating conditions, producing PO with water as the only by-product, thus minimizing environmental impact. This study focuses on process intensification and optimization of the Hydrogen Peroxide to Propylene Oxide (HPPO) process, with the goal of improving energy efficiency, enhancing mass utilization, optimizing reactor operating conditions, and minimizing waste generation through targeted process modifications. The results demonstrate that the HPPO process is a sustainable and economically viable option for small to medium-scale PO production, aligning with green chemistry principles and industrial scalability. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).